Seasonal and diel activity patterns of the Balkan chamois in Greece: first insights from camera trap data - Konstantinos Papakostas; Haritakis Papaioannou; Athanasios Gerogiannis; Athanasios Korakis; Anastasios Pappas; Vassiliki Kati (Mammal Research, 2026)
This study presents the first assessment of the activity patterns of the Balkan chamois ( Rupicapra rupicapra balcanica ) in Greece using camera traps, with a focus on potential differences between forested and open habitats. We deployed 49 camera traps across northwestern Greece (2015–2020), targeting areas with high chamois presence. Thirty-nine cameras yielded usable data (6,152 camera days). We analyzed seasonal and diel activity patterns based on independent photographic events. Chamois had a daily activity ranging from 9:00 to 21:00 and a peak at 11:00. The species used both forested and open areas, but we found no substantial differences in their activity patterns between the two. Nocturnal activity was generally low but increased during autumn in open areas, coinciding with the rutting season. We recommend a systematic camera trap deployment in future studies to evaluate activity overlap with sympatric species and the effects of human disturbance on chamois behavior.

Efficiency of alternative intensity measures for the seismic assessment of monolithic free-standing columns - Athanasios Pappas; Anastasios Sextos; Francesca da Porto; Claudio Modena (Bulletin of Earthquake Engineering, 2017)